Maximal Cytoreduction in Patients With FIGO Stage IIIC to Stage IV Ovarian, Fallopian, and Peritoneal Cancer in Day-to-Day Practice: A Retrospective French Multicentric Study. Issue 8 (1st October 2012) - Luyckx, Mathieu; Leblanc, Eric; Filleron, Thomas; Morice, Philippe; Darai, Emile; Classe, Jean-Marc; Ferron, Gwenaël; Stoeckle, Eberhard; Pomel, Christophe; Vinet, Bénédicte; Chereau, Elisabeth; Bergzoll, Cécile; et al.
Abstract : Objectives: To evaluate the outcome of maximal cytoreductive surgery in patients with stage IIIC to stage IV ovarian, tubal, and peritoneal cancer regarding overall survival (OS) and disease-free survival (DFS). Materials and Methods: Five hundred twenty-seven patients with stage IIIC (peritoneal) and stage IV (pleural) ovarian, fallopian tube, and peritoneal carcinoma underwent surgery between January 2003 and December 2007 in 7 gynecologic oncology centers in France. Patients undergoing primary and interval debulking surgery were included, whichever the number of chemotherapy cycles. The extent of disease, type of surgical procedure, and amount of residual disease were recorded. A multivariate analysis of the outcome was performed, taking into account the stage, grade, and timing of surgery. Results: Median DFS was 17.9 months, but median OS was not reached at the time of analysis. Complete cytoreductive surgery, without evident residual tumor at the end of the procedure, was obtained in 71% of all patients (primary surgery, 33%). After neoadjuvant therapy, the rate of complete debulking surgery was higher (74%) compared to primary cytoreductive surgery (65%). Twenty-three percent of patients needed "ultra radical surgery" to achieve this goal. The most significant predictive factor for DFS and OS was complete cytoreductive surgery compared to any amount, even minimal (1–10 mm), of residual disease. In the group of patients with complete cytoreductive surgery, the patients undergoing surgery before chemotherapy showed better DFS than those having first chemotherapy. Conclusion: The findings confirm that complete cytoreduction is the criterion standard of surgery in the management of advanced ovarian, peritoneal, and fallopian tube cancer, whatever the timing of surgery. With experienced teams, surgery was completed, without evident residual tumor in 71% of the cases.